A Multicentre Randomized Clinical Trial on Efficacy and Safety of Huxin Formula in Patients Undergoing Percutaneous Coronary Intervention. (26th May 2014) - Wu, Huan-Lin; Wang, Yun-Fei; Li, Jun-Zhe; Zhang, Min-Zhou; Sheng, Xiao-Gang; Wang, Xia; Li, Song; Chen, Qiu-Xiong; Li, Xiao-Qing; Ou, Ai-hua; Ruan, Xin-Min
Abstract : Percutaneous coronary intervention (PCI) is widely used in clinical treatment of coronary artery disease. However, the effects of PCI on preventing restenosis after revascularization and improving the quality of life were not satisfying. Huxin Formula is formulated by modifying an experienced Chinese medicine formula and has been widely used in clinical practice due to its marked effects on coronary heart disease. A multicentre double-blind randomized controlled clinical trial was designed to evaluate the effects and safety of Huxin Formula in patients undergoing PCI. Our results showed that there was no significant difference between the two groups in main outcomes. For patients with ejection fraction (EF) > 50%, score of the quality of life scale was higher in treatment group compared with control group. For patients with unstable angina, score of the quality of life scale in 360 days was significantly higher in treatment group compared with control group (P < 0.05 ). No obvious adverse reaction was found in the use of Huxin Formula. In conclusion, Huxin Formula, believed to be a safe treatment for patients after PCI, has benefits in improving the quality of life in patients with unstable angina though it failed to show superiority in primary and secondary outcomes.